Utilizing Internal Hemostatic Nets for Rhytidectomy in Fitzpatrick Skin Types III to V - Saha, Shivangi; Gupta, Susmita; Singhal, Maneesh; Vij, Vikesh; Parashar, Sanjay (Indian Journal of Plastic Surgery, 2025)
Hematoma is a common and concerning complication following facelift surgery. To mitigate this risk, hemostatic nets can be applied either externally or internally. In patients with Fitzpatrick skin type of or greater than III, chances of dyspigmentation after external sutures are high for which internal quilting sutures (IQS) have emerged as a promising tool. There is lack of evidence on the use of IQS in darker skin types. Here, we aim to demonstrate its technique and efficacy.Forty-one individuals with Indian/Middle Eastern ethnicity, Fitzpatrick skin type ≥III underwent facelift surgery between February 2019 and October 2024. The platysma superficial musculoaponeurotic system plication facelift procedure was performed. IQS were then applied using 4–0 Vicryl, between subcutaneous tissue and skin. Patient demographic data, details of the procedure, early complications including hematoma, necrosis, bruising, nerve palsy, and late complications like skin dimpling, seroma, and sialorrhea were recorded.The patient cohort comprised 6 males and 35 females (mean age: 55 years), among which 13 patients were of Mediterranean/Middle Eastern ethnicity and 28 were Asian. Fitzpatrick skin type III was present in 17 patients, type IV in 20 patients, and type V in 4 patients. The mean follow-up duration was 37.2 months. No cases of hematoma or seroma were recorded. There was one case of dehiscence in a smoker patient with diabetes. Transient dimpling was observed in seven patients, and two patients developed dog-ears; both resolved conservatively.In the external hemostatic net, visibility of sutures and increased risk of dyspigmentation at needle puncture sites can be distressing. IQS maintain the benefits of external hemostatic nets—such as reducing skin tension and enhancing redraping—without its disadvantages, resulting in more natural and lasting outcomes, especially for patients with thicker skin and higher Fitzpatrick skin types.
Keywords: quilting sutures; platysma; SMAS; Indian skin; facelift; hyperpigmentation